Epidemiology and public health challenges of echinococcosis in the Republic of Moldova - Sîrbu Alexandru; Spătaru Diana (Acta Marisiensis - Seria Medica, 2025)
Objective: This study aims to analyze the current epidemiological trends of echinococcosis in the Republic of Moldova and evaluate the effectiveness of existing surveillance and control measures.